2013
DOI: 10.1021/jo3024889
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Bis-triazolyl Benzochalcogendiazole Cycloadducts as Tunable Metal Ion Sensors

Abstract: A series of bis-triazolyl benzochalcogendiazoles was synthesized to investigate their metal-binding capabilities. These fluorophores were formed through the cycloaddition of an ethynylated benzochalcogendiazole and a water-soluble azide. Variation of the chalcogen heteroatom was seen to affect the photophysical properties as well as the metal-binding activity. These cycloadducts exhibited a distinct response to Cu(2+), Ni(2+), and Ag(+) in water. The binding affinity for the copper and nickel ions increased mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…In particular, the triazole‐extended dithiazolophospholes provide a suitable N,N‐chelating moiety for metal‐ion binding. Similar chelating triazole systems for metal‐ion sensing have recently been reported by Bunz and co‐workers 26…”
Section: Resultssupporting
confidence: 71%
“…In particular, the triazole‐extended dithiazolophospholes provide a suitable N,N‐chelating moiety for metal‐ion binding. Similar chelating triazole systems for metal‐ion sensing have recently been reported by Bunz and co‐workers 26…”
Section: Resultssupporting
confidence: 71%
“…Therefore, Bunz et al developed water-soluble fluorescent molecules possessing oligo-(ethylene oxide) substituents attached to the heteroaromatic core via a 1,2,3,-triazole linkage. 37 Thus, three bis-triazolyl benzochalcogendiazoles were synthesized to investigate their metal ion-complexation abilities (see Figure 13a). 37 These fluorophores were formed by the CuAAC cycloaddition between the ethynylated benzochalcogendiazole and water-soluble azidated oligo(ethylene oxide)s. Variation in the chalcogen heteroatom was found to affect the metal-complexation activity.…”
Section: Chemosensors Based On Cuaacmentioning
confidence: 99%
“…37 Thus, three bis-triazolyl benzochalcogendiazoles were synthesized to investigate their metal ion-complexation abilities (see Figure 13a). 37 These fluorophores were formed by the CuAAC cycloaddition between the ethynylated benzochalcogendiazole and water-soluble azidated oligo(ethylene oxide)s. Variation in the chalcogen heteroatom was found to affect the metal-complexation activity. It was clearly shown that the triazole rings are complexation sites for specific metal ions as shown in Figure 13b.…”
Section: Chemosensors Based On Cuaacmentioning
confidence: 99%
“…Reaction of aromatic and heteroaromatic ortho-diamines and selenium dioxide was conducted in solid state, 204,205 in ethanol, 20,[206][207][208][209][210][211][212] in acetic anhydride, 213 and even in water. [214][215][216] Typical examples of fused 1,2,5-selenadiazoles prepared are given in Figure 6 (solvents used and yields of selenadiazoles are shown below the formulae).…”
Section: Scheme 93mentioning
confidence: 99%
“…253 Statistical analysis of the spectrophotometric response of bis-triazolyl benzoselenadiazole 223 to the different metal ions resulted in a sensitive and selective sensor for silver, copper and nickel, ideal for use in aqueous systems ( Figure 11). 210 …”
Section: Analytical Chemistrymentioning
confidence: 99%